English hashtag as an object of linguistic study - Рябова, К. О. (Studia Philologica, 2019)
The popularity of a hashtag is rising up every day. We use the hashtags to mark our messages or to find the information in the Internet. The hashtag has attracted attention not only Internet users but also scientists. The article focuses on the theoretical background and the approaches to the research of the hashtag as a kind of microtext. The author provides theoretical information about text and microtext, their main characteristics and classification as well as outlines the main linguistic features of the hashtag in the social networks Twitter, Facebook and Instagram. We have considered the etymology of “hashtag” and analyzed the previous works. The article presents the characteristic differences of microtext on phonetic-grapheme, lexical, syntactic levels. It is highlighted variation of pronunciation, graphic and phonetic substitutions, and spelling mistakes. The paper investigates various aspects of using microtext in the social networks.